The Use of stem cells in burns treatment - Brzozowska, Monika; Wardal, Wiktoria; Furlepa, Natalia; Rzenno, Robert; Wojciechowska, Karolina; Matuszewska, Marcelina; Wicha, Katarzyna; Sidz, Natalia; Tomaszewska, Magdalena; Jedlikowska, Wiktoria (Journal of Education, Health and Sport, 2025)
Introduction and purpose: Burns are a real problem that can result in long hospitalization and scarring. Stem cells (SCs) have been shown to have a number of actions that accelerate and improve the healing process. The aim of this review is to explore the stem cell mechanisms that can be used to improve burn healing Materials and methods: A comprehensive analysis of articles available on PubMed and Google Scholar was undertaken by entering keywords in appropriate configuration: Stem cells/ burn wound/ wound healing/ mesenchymal stem cells. Description of the state of knowledge: In the physiological process of wound healing, migration and proliferation of stem cells initiate epithelialization. The therapeutic use of stem cells has many beneficial effects. Their regenerative potential is superior to conventional treatments. Stem cells due to their ability to differentiate, autocrine and paracrine activity and immunomodulatory activity - accelerate the wound healing process, promote cell proliferation, collagen production, regulate inflammation, prevent hypertrophic scarring, stimulate re-epithelialization, angiogenesis and granulation. Conclusion: The mechanisms of action of stem cells appears to be promising in the context of treating burn wounds, but in order for them to fully replace current treatments, a deeper understanding of the complex biological mechanisms and further studies are needed to evaluate the efficacy and safety of different types of stem cells and to identify the most suitable ones.